Isolation and Identification of Staphyococci from Raw Milk of Cows Infected with Mastitis - Al-Taan, Safana, A.S. (The Iraqi Journal of Veterinary Medicine, 2003)
Twenty-six isolates of staphylococci were recovered from of 100 raw milk samples collected from one hundred cows infected with mastitis. For the isolation of bacteria, Mannitol salt agar was used as a selective medium. Staphylococcal species were identified by API-STAPH system. The identified species were: - Staphy aureus (13), Staph. epidermidis(9), Staph. haemolyticus(2), Staph. lugdunensis()), and Staph. hominis). Staphylococcus aureus was the most prevalent pathogen among other Staphyloccocal species isolated in this study. Staph. aureus isolates revealed positive results for the defection of capsule structure and for production of some essential enzymes such as coagulase, phosphatase, DNA ase and haemolysin which are highly associated with the virulance of bacteria. Staph. aureus isolates were tested for their sensitivity to the antibiotics and the results were: 13(100%) isolates were sensitive to Gentamycin and Tetracyclene, 11 (84.6%) isolates were sensitive to Oxacillin, Penicillin, Ampicillin, Erythromycin and Cephalexin, where as only 2 (15.4%) isolates were Methicillin Resistant Staph. aureus (MRSA) which showed multi -resistant towards many antibiotics used in this work.